IDENTIFIKASI ETNOSAINS DALAM KEARIFAN LOKAL MALOMANG SEBAGAI SUMBER BELAJAR IPA - Hartica Putri Ardana; Aldeva Ilhami; Diniya Diniya; Munawwarah Munawwarah (Journal of Chemistry Education and Integration, 2023)
This study aims to identify the process of making ethnofood lomang and the scientific elements contained in this traditional food culture. The research used is descriptive qualitative research with a case study method or approach. Data collection techniques using observation and interview methods. The results of the study show local wisdom to know the process of making lomang. The process of making lomang through several stages. Among them are the selection of tolang bamboo and banana shoots, and the washing of tolang bamboo and pulut rice. Furthermore, before the roasting process, the lamang to be burned must be given coconut milk and first tied the top of the excess banana leaf at the base of the bamboo. Keywords : Local Wisdom, Ethnoscience, Ethnofood for Making Lomang, Science Learning